The Importance Of Microsilicate As An Active Mineral Supplement In Cement Production (Eurasian Research Bulletin, 2023)
In the scientific laboratories of the world's leading research centers and universities, much research is underway to study mineral binders and materials based on them, reduce carbon dioxide emissions to the environment in the cement production process, and make the most of the use of local raw materials and the activation of waste, chemical additives and mechanics in industrial cement production. In this regard, it is important to develop optimal compositions of low-demand water bindings, energy-efficient building materials that allow you to ensure the transparency of the portland cement clinic in the production of cement using local raw materials and technological waste, as well as surfactants. in scientific research in this regard.